The development of a discrete-point test to measure the fourth year high school students' writing skills - Salvilla, Mime Teresita Maravilla 1947-
This study aimed to develop a Discrete- Point Writing Test that would measure fourth year high school students' writing skills. The original test consisting of 130 items was administered to 238 fourth year high school students of the Iloilo School of Arts and Trades. It aimed to show the validity and reliability of the said test as an appropriate objective evaluative device for senior secondary school students for whom it was specifically designed.